Sustainable Development in Slovak Retail Practice - Lieskovská, Vanda (Publishing House of Wroclaw University of Economics and Business, 2025)
The issue of sustainable development in Slovak retail practice is the subject of chapter paper. The introduction discusses the importance of retail and presents sustainability alternatives, placing emphasis on the interconnection of environmental, social and economic sustainability. Next, the author addressed selected sustainable strategies in retail, which can intersect with each other. Sustainable products offered in retail are also related to their origin, assortment, structure, as well as their quality and labelling, followed by the issue of the circular economy and efforts to reduce waste. The next section deals with Slovakia’s experience in implementing the programme of depositing disposable packaging, which has been operating since January 2022, focusing on aligning the interests of participants in the used beverage packaging collection system. In the conclusion, selected examples of good practice in Slovak retail are presented in terms of applying the principles of sustainable development.
Quote as: Lieskovská, V. (2025). Sustainable Development in Slovak Retail Practice. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 227-239). Publishing House of Wroclaw University of Economics and Business.
Keywords: retail; sustainable development; circular economy; deposit system